Literasi Sistem Pembayaran Quick Response Code Indonesian Standard (QRIS) pada Siswa Sekolah Menengah Atas di Pekanbaru - Umi Rachmah Damayanti; Ade Ria Nirmala; Ratna Nurani; Chelly Natalia Kuswara (Institut Riset dan Publikasi Indonesia (IRPI), 2023)
Quick Response Code Indonesia Standard (QRIS) stands for QR Code Indonesia Standard, QRIS is the first step of the digital transformation of the Indonesian Payment System (SPI), which is believed to support the acceleration of economic development and digital finance in Indonesia. Bank Indonesia made QRIS easier for people to make non-cash payment transactions. Applying QRIS to the people of Indonesia will take a long time, especially in remote areas or small cities. This is because the level of digital financial literacy in Indonesia, especially in regions or small cities, is still shallow. Therefore, it takes constant education and socialization at various levels of Indonesian society so that QRIS can run optimally. High school students are a group of people who are very digitally active. Almost all activities, whether school, community, or consumption, are internet-based. Considering these conditions, it is necessary to conduct socialization activities using QRIS for high school students to manage personal finances, especially in decisions regarding consumption, savings, and investment activities. The community group targeted as a strategic target group is high school students. The consideration for this target group is that high school students are a group of people who are very active in using gadgets and the internet. Almost all activities of these high school students are carried out digitally.